2019
DOI: 10.15562/bmj.v8i3.1569
|View full text |Cite
|
Sign up to set email alerts
|

A case evaluation of traumatic brain injury in Wahidin Sudirohusodo Hospital, Makassar during January 2016 - December 2017

Abstract: Introduction: Traumatic Brain Injury is a case that is often encountered in emergency care installation and is one of the leading causes of death in the productive age range. Globally, the Traumatic Brain Injury incident increased sharply, mainly due to the increase in motorized vehicle use. In 2020,  the WHO estimated that traffic accidents would be the third-largest cause of disease and trauma in the world. In Indonesia, at Cipto Mangunkusumo Hospital Jakarta shows that the mortality rate is high in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the adult population, the greater tendency to perform outdoor activities among men than women raises men's risk of experiencing traffic accidents, which is the leading cause of brain injury in developing countries (42.4%) [8], [9]. In developed countries, where the top cause of brain injury is falls, men also have a greater risk of brain injury than women [4], [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the adult population, the greater tendency to perform outdoor activities among men than women raises men's risk of experiencing traffic accidents, which is the leading cause of brain injury in developing countries (42.4%) [8], [9]. In developed countries, where the top cause of brain injury is falls, men also have a greater risk of brain injury than women [4], [10].…”
Section: Discussionmentioning
confidence: 99%
“…Managing TBI can involve surgical interventions (e.g., evacuation and decompressive craniotomy) and/ or conservative interventions without surgery (e.g., oxygenation, resuscitation, antibiotics, osmotherapy, and analgesics) [3], [4]. Decompressive craniotomy is an intervention in which a part of the skull is removed and the dura mater is expanded to allow the brain to swell without crushing it or causing herniation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this research focuses on reducing the mortality from AEDHs by providing quick referrals to emergency neurosurgery and sufficient hospital facilities for continuous access to these services for those with head injuries. 14 In underdeveloped countries with insufficient manpower and a lack of key diagnostic imaging support services, variables such as delayed detection and seeking appropriate professional care may also have an indirect impact on the fate of these patients. 13 The purpose of this article is to present an overview of the severity and outcomes of TBI induced by EDH cases in Asian nations, as well as to address some of the public health ramifications of this burden which is the most dangerous threatens the life of the victims.…”
Section: Treatmentmentioning
confidence: 99%
“…Traumatic brain injury (TBI) is a complicated condition that is the primary cause of death and disability in children and young adults in developed countries [ [1] , [2] , [3] ]. In 2019, Dewan et al conducted a systematic review and the results found that 69 million (95% CI 64–74 million) people worldwide will experience brain injury each year.…”
Section: Introductionmentioning
confidence: 99%